Improving the nutritional status of school children through the formation of a group of children caring for nutrition in SD Az- Zakiyah Islamic School - Nasution, Ernawati; Ardiani, Fitri; Sudaryati, Etti (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
This service activity is a training for school children to care about their food consumption and nutritional status.. This service activity carried out at SD Az-Zakiyah Islamic School Medan aims to provide understanding to school children about healthy, nutritious, and balanced food, as well as weight and height measurement skills. The methods used are lectures, practice of measuring body weight and height using microtoas and digital scales, and the practice of introducing food ingredients that contain nutrients using a food model. The t test results showed that there was a significant difference (p = 0.005) in children's knowledge before and after providing information. This shows that this training provides increased knowledge of school children. It is hoped that the training participants will later become nutritional ambassadors who can disseminate information about healthy, nutritious, and balanced food and the importance of monitoring nutritional status from an early age to their friends, especially at school and in the environment around their homes in an effort to improve nutritional status in school children. In addition, I hope this program will be sustainable and will raise awareness among school foundations and health centers to support this activity which has been initiated in college.